After Empire : Scott, Naipaul, Rushdie - Gorra, Michael Edward (University of Chicago Press, 1997)
In After Empire Michael Gorra explores how three novelists of empire, Paul Scott, V.S. Naipaul, and Salman Rushdie, have charted the perpetually drawn and perpetually blurred boundaries of identity left in the wake of British imperialism. Arguing against a model of cultural identity based on race, Gorra begins with Scott's portrait, in The Raj Quartet, of the character Hari Kumar, a seeming oxymoron, an "English boy with a dark brown skin," whose very existence undercuts the belief in an absolute distinction between England and India.